Sorption extraction of and radionuclides from aqueous solutions by MnO(OH) nanoparticles - AP Krasnopyorova; DS Sofronov; AM Odnovolova; NV Efimova; GD Yuhno; OS Kogol (Adsorption Science & Technology)
In this study, nano-sized particles of manganese oxyhydroxide (MnO(OH)) are synthesized. Sorption properties of this material towards 90 Sr and 137 Cs radionuclides in the pH range from 2 to 9 at a temperature of 293.15 K solution are studied. The time of sorption achievement equilibrium in the radionuclide sorbent system depends on the nature of sorbed cation, but does not exceed 60 min.